Non‐muscle invasive bladder cancer and bacillus Calmette‐Guerin treatment: a review of the literature. Issue 2 (14th October 2014) - Alcorn, Jason; Burton, Rob L; Topping, Annie
ABSTRACT Bladder cancer is the second most common urological cancer in the UK, with over 10 000 cases diagnosed annually. With 80% of urothelial bladder cancers being non‐muscle invasive, it is important to understand the treatments available. This review aims to identify and review the literature regarding bacillus Calmette‐Guerin (BCG) treatment. An integrative‐based review was conducted to generate a broad overview of the existing knowledge for BCG treatment. An open search of online databases was conducted to identify articles published in English from the earliest date available to September 2013, using key terms related to BCG. A significant number of articles were identified. To narrow the results and identify the most relevant articles, the search terms were cross‐referenced. The resulting articles were then reviewed using the critical appraisal skills programme framework. The tools provided by CASP give a systematic, transparent and rigorous approach to the quality assessment of research studies. The research articles were then categorized under the following headings: side effects, including local, systemic and age; quality of life; and attrition. The major conclusion from this literature review is that BCG treatment, when given through an induction and maintenance regime, significantly reduces the risk of progression and recurrence. However, there are potential side effects which the patient and the nurse need to be aware. This review also highlighted that there is a lack of research from the UK and that there is a paucity of research showing why patients withdraw from BCG treatment